2008
DOI: 10.1097/adm.0b013e31818a6596
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Abstinence in Opioid-Dependent Patients

Abstract: : Considering the results it seems not possible to predict who will be abstinent or not 1 month after detoxification. Because rapid detoxification is found to be an effective detoxification method in selected patients, it seems warranted to recommend that patients with similar characteristics (ie, patients motivated for an abstinence-based treatment and low non-drug-related severity scores on the ASI) should be regarded as eligible for rapid detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Paradoxically, one recent study reported that poor sleep during opioid detoxification was associated with abstinence during a 4-week follow-up period 50. The authors speculated that treatment staff may have given more attention to poor sleepers, resulting in better outcomes, but they could not support that explanation with data.…”
Section: Evidence That Sleep Predicts Relapse Across Psychoactive Submentioning
confidence: 98%
“…Paradoxically, one recent study reported that poor sleep during opioid detoxification was associated with abstinence during a 4-week follow-up period 50. The authors speculated that treatment staff may have given more attention to poor sleepers, resulting in better outcomes, but they could not support that explanation with data.…”
Section: Evidence That Sleep Predicts Relapse Across Psychoactive Submentioning
confidence: 98%
“…Sleep disturbance has been identified as a risk factor for relapse in addiction to a range of substances (see Brower & Perron, 2010 for review), including alcohol (Brower, Aldrich, & Hall, 1998), nicotine (Boutou et al, 2008), and cocaine (Sofuoglu et al, 2005). Much less work has documented the role of sleep in relapse in the context of opioid dependence (see Dijkstra et al, 2008 for an exception) despite observations of sleep disruption during opiate withdrawal (Wang & Teichtahl, 2007). To gain further insight into the effects of sleep disruption in patients in treatment for NMUPD, this study examined the effects of sleep quality on craving – a proximal outcome associated with subsequent opioid use (Tsui et al, 2014) – through the indirect associations with positive affect (PA) and negative affect (NA) at the day-to-day, within-person level.…”
Section: Introductionmentioning
confidence: 99%
“…Variables of interest included socio‐demographic and clinical characteristics that have shown to influence opioid withdrawal expression and/or naltrexone induction, including age, gender, injection drug use (IDU), daily quantity, and time from last use at admission . Exploratory analyses were conducted by using Spearman correlation coefficients to assess the nature of potential relationships between day‐2 withdrawal changes, behavioral and biological variables, and induction onto XR‐NTX.…”
Section: Methodsmentioning
confidence: 99%